Formulasi dan uji sifat fisik lulur krim ekstrak etanol bunga kecombrang (Etlingera eliator (Jack) R.M. Smith) - Rina Kurniaty; Asri Ainun; Mutia Farida; Saiful Azhari; Salman Salman; Mahmudi Mahmudi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Kecombrang plant (Etlingera eliator (Jack) R.M. Smith), has bioactive compounds of polyphenols, alkaloids, flavonoids, steroids, saponins and essential oils. The purpose of this study, to make a cream scrub formulation from ethanol extract of kecombrang flowers that meets the standards and benefits on the skin. The method of this study, by varying the concentration of ethanol extract of kecombrang flowers 5% and 10% with modified formulations adding amylum oryzae as a scrub and without the addition of amyulum oryzae. The results of the 28-day study based on the parameters, in the organoleptical test had a stable shape, odor, and color, in the homogeneity test showed a homogeneous preparation, the pH test had a stable value of 7, the spreadability test had an average value of 5 cm, stable results in room or low temperature storage (2-8oC). Hedonic test results with parameters, aroma, texture, color, and effectiveness, namely formulation I 10% with an average scale value of 5, which means very like is a formulation with the addition of amylum oryzae as a scrub. Formulation results with the addition of amylum oryzae affect the preparation of abrasive formulations. The results of the skin effectiveness test, in the moisture test using a skin analyzer with an average value of moist volunteer skin at week 4, and the volunteer's skin color is slightly brighter. In conclusion, the cream scrub formulation has a good formulation, kecombrang flower extract has the effect of brightening the skin and moisturizing the skin.